Analysis of Member Satisfaction Levels Regarding the Quality of Cooperative Services: The Case of the Karya Mekar Farmers' Cooperative in Selajambe Village, Selajambe District, Kuningan Regency - Alan Ruslani; Bambang Kurniawan; Nono Suyono; Achmad Faqih; Yayat Rahmat Hidayat (Journal of World Science, 2025)
Indonesia has three main economic sectors: the state, the private sector, and cooperatives, which work together to create a strong economy. Cooperatives play a role in enhancing the welfare of their members and balancing capitalism while focusing on improving farmers' incomes. The performance of cooperatives needs improvement through both financial and non-financial measures. Member satisfaction affects the image of the cooperative, which in turn increases participation and loyalty, influenced by characteristics such as age and education. This study uses a survey method to evaluate service performance and measure member satisfaction in the Karya Mekar Farmers' Cooperative, Selajambe Village, Kuningan Regency, from October to December 2024. The data used consists of primary data obtained through interviews and questionnaires, as well as secondary data from management reports, Annual Member Meetings, and related agencies, which includes information on the number of members, cooperative development, and organizational structure. The analysis of service quality performance employs the IPA (Importance-Performance Analysis) method, which assesses the importance and performance levels of service attributes based on five characteristics. Measurement is conducted using a five-point scale (Likert scale) that describes attitudes such as agreement-disagreement, satisfaction-dissatisfaction, and good-bad. The level of member satisfaction in the cooperative is analyzed using the CSI and SERVQUAL methods. SERVQUAL assesses both the level of expectations and actual performance/perception, while CSI is used to measure the percentage of member satisfaction levels.